GAMBARAN KADAR LIPOPROTEIN a TERHADAP PERBEDAAN DOSIS OBAT ANTIEPILEPSI - I Dewa Gede Suci Indra Wardhana,* Aris Catur Bintoro,** Dodik Tugasworo** (NEURONA, 2016)
INTRODUCTION EPILEPSY IS A DISEASE THAT REQUIRES LONGTERM THERAPY USING ANTIEPILEPTIC DRUGS AEDS TREATMENT WITH OAE OLD GROUP SUCH AS PHENYTOIN PHT CARBAMAZEPINE CBZ AND VALPROIC ACID VPA HAD METABOLIC EFFECTS IN CLUDING ALTERATION ON LIPID AND LIPOPROTEIN A LP A LEVELS INCREASING OF LPA LEVELS MORE THAN 30MGDL WAS A RISK FACTOR OF ATHEROSCLEROSIS